PENERAPAN ELEMEN HIAS PADA INTERIOR MASJID AL AKBAR SURABAYA - Wardani, Laksmi Kusuma; Gustinantari, Arinta Prilla (Institute of Research and Community Outreach - Petra Christian University, 2008)
The Al Akbar Mosque in Surabaya applies ornaments in its interior design. In Islamic teachings, the prohibition in using human and animal visualization has thus arised several kinds of Islamic ornaments that can be used as a measure in mosque interior implementations. Islamic ornaments in the mosque can be seen in the interior elements and facilities (furniture) supporting human activities and possess values and meanings according to Islamic concepts. This research aims to observe whether the ornament implemenations in Al Akbar Mosque used are according to Islamic rules. The results show that the interior of Al Akbar Mosque apply Islamic principles such as geometric patterns, Arabic calligraphy, Arabesk patterns and lighting systems that are according to Islamic values. The implementation of ornaments are in line with Islamic rules. This means that the designing of this place of worship as a process of actualizing physical concepts has analyzed the requisites of religious teachings as well as the worship activities as basic determinations of ornament implementations in interior design. Abstract in Bahasa Indonesia: Masjid Al Akbar Surabaya menerapkan elemen hias pada interiornya. Dalam Islam ada larangan visualisasi manusia dan hewan, sehingga muncul jenis elemen hias khas Islam yang bisa dijadikan tolok ukur dalam penerapannya pada interior masjid. Penerapan elemen hias Islam pada masjid dapat dilihat pada unsur interior dan fasilitas penunjang kegiatan (perabot). Peletakkan pada tiap-tiap bidang tersebut mempunyai makna yang sesuai dengan konsep Islam. Oleh karena itu, penelitian ini bertujuan mengetahui apakah elemen hias yang diterapkan pada interior Masjid Al Akbar Surabaya sudah sesuai dengan aturan-aturan Islam. Hasil penelitian menunjukkan bahwa interior Masjid Al Akbar Surabaya menerapkan elemen hias Islam yaitu pola geometris, kaligrafi Arab, pola Arabesk, dan menampilkan pencahayaan yang sesuai dengan nilai-nilai Islami. Penerapan elemen hias ini sudah sesuai dengan aturan-aturan Islam, yang berarti merancang ruang ibadah sebagai proses perwujudan konsep fisik telah mengupas persyaratan ajaran agama maupun prosesi kegiatan sebagai dasar penentu perwujudan unsur elemen hias pada interior. Kata kunci: Masjid, interior, elemen hias